itu PENGARUH YOGA TERHADAP PENURUNAN TINGKAT KECEMASAN PADA WANITA PREMENOPAUSE DI PMB SUMIYATI - Titin Apriyani; Ade Marlisa Rahmadayanti; Rani Purwani (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Premenopause is a transitional period between the reproductive period and the senium period. This period is called climacteric which is about 4 to 5 years before menopause. Premenopause is the entire fertile period before menopause occurs, namely the period from menarche to menopause. Symptoms in premenopausal women are feeling hot flashes, anxiety, insomnia, irritability, often forgetting. Anxiety that occurs in premenopausal women is something that is naturally experienced by every woman. Anxiety occurs because of the physical changes faced by most premenopausal women. One of the sports that can be done in premenopausal women is yoga. Yoga exercises balance the autonomic nervous system and are beneficial for lowering blood pressure. The purpose of this study was to determine the effect of yoga on reducing anxiety levels in premenopausal women at PMB Sumiyati in 2023. This study used a pre-experimental research design with a one group pre-post test design, which did not use a control group. The population in this study were women aged 40-50 years in the PMB Sumiyati area, with a sample of 10 respondents. The instrument used is a questionnaire. The results of the study of 10 respondents who had participated in yoga regularly showed that there was a decrease in anxiety levels compared to before doing yoga. Based on the results of the Chi Square Statistical Test, the p value = 0.002 <α = 0.05. This shows that there is an effect of yoga on reducing anxiety levels in premenopausal women at PMB Sumiyati in 2023.